Le "De paenitentia" du Pseudo-Éphrem "Plerique cernimus" (CPL 1143a) refonte (wisigothique?) du "De reparatione lapsi" de Bachiarius - Bogaert, Pierre-Maurice 1934- (Revue bénédictine, 2017)
Pseudo-Ephrem’s De paenitentia (CPL 1143a) is a rewriting of Bachiarius’s De reparatione lapsi. It is cited by Beatus de Liebana, Florus, and in a manuscript of Moissac, inside a commentary of I-IV Regum by Raban Maur. Bachiarius was writing on a personal case, in order to recommend leniency ; Pseudo-Ephrem argues in the same direction, for a large public. The author of the De paenitentia, to be placed in Spain or in Septimany after Bachiarius and before Beatus, is opposed to an influent rigorist trend and reveals the persistance of a peculiar type of asceticism, whose Bachiarius was already a witness. The edition of Assemani, 1746, based on one late manuscript and reprinted in PLS 4, 617-640, may be substantially improved.